Environmental Vulnerability Assessment and Stormwater Management to Enhance Watershed Performance. (September 2020) - Prastica, R M S; Kurniawan, R P; Apriatresnayanto, R
Abstract: The declination of environmental quality triggers several harmful impacts on society, such as the increasing of water-borne diseases, low quality of health, and lousy habitat ecosystem. The research aims to conduct a vulnerability assessment method of a watershed and to perform stormwater management to increase the catchment performance due to dynamic changes. The observation focused on Sugutamu sub-catchment, Depok, West Java. The evaluation includes sub-watershed map compilation, impervious cover calculation, river assessment, and restoration capacity evaluation. The result indicates that the sub-catchment describes as restorable non-supporting sub-watershed. There are three main regions in the sub-catchment. These areas have a percentage of impervious cover 95.6%, 72.5%, and 38.5%, respectively. Also, according to the future impervious cover prediction, these areas will have 97.8%, 95.3%, and 97.5%, respectively. The paper used the National Stormwater Calculator and EPA SWMM 5.1 software to visualize and to predict the future condition of sub-watershed with the various scenario. The application of low impact development (LID) in the research area declines the level of runoff, enhances the level of infiltration, and reduces the peak discharge. The research concludes that watershed vulnerability assessment, along with stormwater management, could control flooding in urban areas.